Particle and vapor emissions from vat polymerization desktop-scale 3-dimensional printers. - Stefaniak, A. B.; Bowers, L. N.; Knepp, A. K.; Luxton, T. P.; Peloquin, D. M.; Baumann, E. J.; Ham, J. E.; Wells, J. R.; Johnson, A. R.; LeBouf, R. F.; Su, F.-C.; Martin, S. B.; et al. (Journal of Occupational & Environmental Hygiene, 2019)
Little is known about emissions and exposure potential from vat polymerization additive manufacturing, a process that uses light-activated polymerization of a resin to build an object. Five vat polymerization printers (three stereolithography (SLA) and two digital light processing (DLP) were evaluated individually in a 12.85 m3 chamber. Aerosols (number, size) and total volatile organic compounds (TVOC) were measured using real-time monitors. Carbonyl vapors and particulate matter were collected for offline analysis using impingers and filters, respectively. During printing, particle emission yields (#/g printed) ranged from 1.3 ± 0.3 to 2.8 ± 2.6 x 108 (SLA printers) and from 3.3 ± 1.5 to 9.2 ± 3.0 x 108 (DLP printers). Yields for number of particles with sizes 5.6 to 560 nm (#/g printed) were 0.8 ± 0.1 to 2.1 ± 0.9 x 1010 and from 1.1 ± 0.3 to 4.0 ± 1.2 x 1010 for SLA and DLP printers, respectively. TVOC yield values (µg/g printed) ranged from 161 ± 47 to 322 ± 229 (SLA printers) and from 1281 ± 313 to 1931 ± 234 (DLP printers). Geometric mean mobility particle sizes were 41.1–45.1 nm for SLA printers and 15.3–28.8 nm for DLP printers. Mean particle and TVOC yields were statistically significantly higher and mean particle sizes were significantly smaller for DLP printers compared with SLA printers (p < 0.05). Energy dispersive X-ray analysis of individual particles qualitatively identified potential occupational carcinogens (chromium, nickel) as well as reactive metals implicated in generation of reactive oxygen species (iron, zinc). Lung deposition modeling indicates that about 15–37% of emitted particles would deposit in the pulmonary region (alveoli). Benzaldehyde (1.0–2.3 ppb) and acetone (0.7–18.0 ppb) were quantified in emissions from four of the printers and 4-oxopentanal (0.07 ppb) was detectable in the emissions from one printer. Vat polymerization printers emitted nanoscale particles that contained potential carcinogens, sensitizers, and reactive metals as well as carbonyl compound vapors. Differences in emissions between SLA and DLP printers indicate that the underlying technology is an important factor when considering exposure reduction strategies such as engineering controls.